DIET AND REPRODUCTION OF LARGEMOUTH BASS IN A RECENTLY INTRODUCED POPULATION, LAKE BRACCIANO (CENTRAL ITALY) - MARINELLI A.; SCALICI M.; GIBERTINI G. (Knowledge and Management of Aquatic Ecosystems, 2007)
This paper concerns a study of some aspects of largemouth bass ecology in an Italian lake (Lake Bracciano). We assessed the success and possible impact of its recent introduction (1998) upon the fish community. From October 2001 to September 2002, 162 individuals were caught, measured, aged and submitted to biopsy (stomach and gonads were removed). Four age classes, from 0 + to 3 +, were observed in the population. Largemouth bass feeding activity was high in June, mostly eating fish (55.7%), crustaceans (in particular Palaemonetes antennarius, 37.5%), insects (4.5%) and molluscs (2.3%). The G.S.I. values showed an autumnal breeding period (from December to February) rather than the spring-summer one frequently described in North America. Moreover, bass attained sexual maturity during the second year of life (1 +). These differences could be related to its recent introduction and the apparent success could represent a problem for other species in the Lake.